The transcriptome sequencing analysis reveals immune mechanisms of soybean fermented powder on the loach (Misgurnus anguillicaudatus) in response to Lipopolysaccharide (LPS) infection - Xu, Yayuan; Zhang, Xinxin; Li, Dongqi; Qian, Kun; Liu, Yu; Xu, Tingjuan; Dai, Lishang; Cheng, Jianghua (Frontiers in Immunology, 2023)
The loach (Misgurnus anguillicaudatus), a small commercial fish that is widely cultivated for its high-quality protein, vitamins, minerals, and essential amino acid, is a member of the genus Misgurnus and the family Cyprinidae. In this study, we gave the LPS-injected loach fermented soybean meal and used transcriptome sequencing to investigate the impact of the fermented soybean powder on the loach’s immune system. 3384 up-regulated genes and 12116 down-regulated genes were found among the 15500 differentially expressed genes, according to the results. The differentially expressed genes were shown to be involved in cellular processes, metabolic processes, cellular anatomical entities, and binding, according to the Go functional annotation. Meanwhile, the KEGG enrichment analysis indicated that the soybean fermented powder treated groups showed significant differences in DNA replication, Nucleotide excision repair, Fanconi anemia pathway, and Base excision repair pathways, suggesting that these pathways are closely related to the enhancement of the immune function of loach by soybean fermented powder. The particular conclusions not exclusively can provide a new conception for the rational utilization of soybean fermented powder but also can provide theoretical guidance for the subsequent healthy breeding of loach.